Views of European Drug Development Stakeholders on Treatment Optimization and Its Potential for Use in Decision-Making - Saesen, Robbe; Lejeune, Stéphane; Quaglio, Gianluca; Lacombe, Denis; Huys, Isabelle (Frontiers in Pharmacology, 2020)
Background: The current drug development paradigm has been criticized for being too drug-centered and for not adequately focusing on the patients that will eventually be administered the therapeutic interventions it generates. The drug-driven nature of the present framework has led to the emergence of a research gap between the pre-approval development of anticancer medicines and their post-registration use in real-life clinical practice. This gap could potentially be bridged by transitioning towards a patient-centered paradigm that places a strong emphasis on treatment optimization, which strives to optimize the way health technologies are applied in a real-world environment. However, questions remain concerning the ideal features of treatment optimization studies and their acceptability among key stakeholders. Objectives: The aim of this study was to explore the views of key stakeholders in the drug development process regarding the concept of treatment optimization. Methods: Semi-structured interviews were conducted between December 2018 and May 2019 with 26 participants across ten EU Member States and five different stakeholder groups, including academic clinicians as well as representatives of patient organizations, regulatory and payer authorities, health technology assessment agencies and industry. Results: Based on the input of the experts interviewed, clarification was obtained regarding the optimal features of treatment optimization studies in terms of their conduct, funding, timing, design and setting. Moreover, a number of opportunities and challenges of undertaking such trials were identified. Inter-stakeholder discussion during their design was seen as desirable. There was also broad support among the participants for regulatory measures to facilitate treatment optimization, although there was no agreement on the optimal scale and nature of these initiatives. Furthermore, the interviewees believed that the evidence strength of well-designed treatment optimization studies performed according to rigorous quality standards is greater than or at least equal to that of classical clinical trials. In addition, there was a strong consensus that the results of treatment optimization studies should be taken into account during the decision-making of regulators, payers and/or clinicians. Conclusions: Stakeholders involved in drug development consider treatment optimization studies to be valuable tools to address current evidence gaps and support their implementation into the existing research framework.